PERANCANGAN IDENTITAS PERUSAHAAN DALAM BENTUKSTATIONERY DESAIN DI RUMAH KREASI GRAFIKA - Setiyo Adi Nugroho; Daniel Rudjiono; Febrian Rahmadhika (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
Rumah Kreasi Grafika is a clothing business that was established in 2020. This clothing business is located at Jalan Grafika Raya, Gedawang, Banyumanik District, Semarang City, Central Java. This company still has shortcomings, especially in the field of design, so that marketing is not very successful. This is due to a lack of knowledge about the value of design in a company.The thing that is most prioritized in the design of making this stationery set is to meet the graduation requirements for the final project course and provide a new perspective in utilizing stationery sets as a means of supporting the company's progress. Where is the initial stationery set that has a design value that does not sell well and is still incomplete.In designing the design of a stationery set, it is necessary to choose the type of font, color and also the composition of the design because these three aspects are vital and can have a serious impact on the effectiveness of the stationery set.